Antidiabetic effect of bitter melon/Kerala (Momordica charantia) in alloxan induced diabetic rat (Research in Agriculture Livestock and Fisheries, 2018)
This study aims at investigating the effect of Momordica charantia extract on glucose tolerance and some biochemical parameters in alloxan induced diabetes rat. A total of 150 rats (50 normal rats and 100 alloxan induced diabetic rats) were used for five trials. The rats were divided into three groups for each trial, each containing 10 individuals as follows: Group A: is the control group, Group B as diabetic control group and group C were diabetic rat received bitter melon (Momordica charantia). Then alloxan injection was injected at a dose rate of 150 mg/kg body weight through intra-peritoneal route to each rat to induce diabetes in groups B and C. Aqueous extract of bitter melon (Momordica charantia) were fed by gavage at a dose of 300 mg/kg body weight daily for 21 days in group C. On 15th day blood glucose level and the body weights, biochemical parameters were measured for the first time to ensure diabetic induction. Then all the rats of this group were kept for more 21 days for the treatment of diabetic condition. Alloxan produced a significant increase in serum glucose, triglyceride (TG), total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), Alanine aminotransaminase (ALT) and Aspartate aminotransaminase (AST) and significant decrease in body weight and high density lipoprotein cholesterol (HDLC). Bitter melon treatment reduced non-fasting and fasting glucose level (p